Pregnancy and childbearing among Adolescents and Young Persons Living with HIV: The Case of Chitungwiza, Harare - Norman Makunika; Lianora Manyange (International Journal of Sexual and Reproductive Health Care - Peertechz Publications, 2021)
It is almost four decade into the HIV pandemic, the outlook of the disease has advanced significantly from death sentence to a chronically manageable disease that can be lived with for long time. This evolution was made possible with the advent of antiretroviral therapy which allowed HIV infected children to reach adulthood. However, sexual, and reproductive needs of these generations remain unattended in many countries. The study sought to highlight the sexual and reproductive health issues affecting young people living with HIV in Chitungwiza and Waterfalls communities, targeting HIV positive young people aged 15-24 years. A mixed methods approach was adopted in which, Qualitative and Quantitative research methods were employed. A survey was conducted with 113 young people to quantify sexual and reproductive health issues affecting young people living with HIV (YPLWH). To solicitate community perceptions and opinions on childbearing among the Adolescents and Young persons living with HIV, 8 focus group discussions and key informant interviews were conducted to qualify the data from the survey. The findings indicated that sexual and reproductive health (SRH) knowledge heavily impacts YPLWH' decision to have children. The sources of information may also affect decisions made by YPLWH. Socio-cultural barriers are major inhibiting factors limiting YPLWH and it was also observed that sero-status disclosure has direct impact on decision for condom use. The study recommends that academic research, NGOs, and other stakeholders with support from the Ministry of Health, should conduct more studies on emerging HIV and SRH issues which will help in addressing knowledge gaps and provide evidence-based knowledge in public health. Overall, this will improve the reproductive health outcomes of young people living with HIV.